Women, myth, and the feminine principle - Knapp, Bettina Liebowitz, 1926-2010 (State University of New York Press, 1998)
"The book begins by probing the "Divine Feminine" in Tibet's Gesar of Ling, one of the most fascinating myths of all time. Especially intriguing is the hero's seemingly continuous dependency on the feminine principle for guidance. The heroine in Kalidasa's Sanskrit drama, Sakuntala focuses on the obstacles set in Sakuntala's earthly trajectory, and how these were instrumental in her evolution from the stage of passive, unconscious, and withdrawn archetypal Maiden to that of the conscious, decisive, strong spiritual Mother. To explore the highly complex personalities of Kriemhild and Brunhild in the High German Nibelungenlied is to enter the realm of sun and shadow, the lightened regions of consciousness and the deep interiors of primal darkness. Quiche Mayas's Popul Vuh introduces a primordial couple as active participants in the creation of humankind while Racine's Phaedra projects the dramatist's own gnawing religious conflicts onto his mythical heroine: questions of guilt, remorse, anguish, and fatality/predestination. Yeats's Irish/Celtic feminist and heroine, Deirdre, underscores her inner strength, fortitude, and courage in the face of death while I.B. Singer's "Yentl the Yeshivah Boy" depicts the struggle confronting a young girl from an orthodox Polish Jewish family as she attempts to break out of an ultrapatriarchal society."--Jacket